PENGELOLAAN KAWASAN EKOWISATA MANGROVE DI DESA RAWA MEKAR JAYA KECAMATAN SUNGAI APIT KABUPATEN SIAK - Sahata Leo Ristar Manik; Dadang Mashur (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2020)
The problems on the management of Rawa Mekar Jaya's mangrove ecotourism area is interesting to study because this mangrove ecotourism area has great potential to be developed however the management has not been optimal. The purpose of this study was to determine the management of mangrove ecotourism in Rawa Mekar Jaya Village, Sungai Apit District, Siak Regency. This research uses descriptive qualitative research methods through data collection techniques by observation,interviews, and documentation in the form of pictures or tables. The results of this study are based on management theory according to Geroge R. Terry, which includes planning, organizing, implementing, monitoring. As for the informants in this study were the Village Head, POKDARWIS, Community, and Tourism Office of Siak Regency. The implementation of Rawa Mekar Jaya mangrove ecotourism management has not been going well such as organizing is still not optimal seen from many people who are no longer active in management, government oversight has not been routinely obstacles are also found in the implementation of ecotourism management, namely budget constraints, lack of government participation, lack of human resource capabilities in the field of tourism and lack of facilities and infrastructure.Keywords: Management, Ecotourism, human Resources